(Re)vendo as páginas, (re)visanado os laços e (des)atando os nós: as relações literárias e culturais Luso-Brasileiras através dos periódicos portugueses (1899-1922) - Müller, Fernanda Suely (2011)
Historically, in Brazil and Portugal, the beginning of the twentieth century is considered as a very significant moment for both countries, a situation that is explained not only if we observe each internal peculiarity of those nations, but also what concerns the relations between them, especially in the cultural sphere. Although it may seem incongruous, especially in the first twenty years, we observed both a growing opposition to the Lusitanian presence (especially in the city of Rio de Janeiro), and a big promotion of "agreements" and "projects" that aimed getting Portugal and Brazil closer to one another through the press. Therefore, we intend to show in this work a short overview of these relationships through the analysis of some Portuguese magazines that circulated in Brazil (such as Brasil-Portugal, Atlântida, Orpheu, A Rajada and Nação Portuguesa, for example), and that aimed also to help the Brazilian public reduce the "mutual ignorance" between the nations mentioned by these publications. To that end, we first proceeded with the compilation and cataloging of articles about the Luso- Brazilian theme, which were extracted from the chosen magazines, to integrate our corpus and, in a second step, we analyzed more thoroughly the articles that we considered to be the most significant ones. Finally, when we identified some causes and justifications presented by the Portuguese press to ratify that constantly "Luso-Brazilian friendship", which was seen as inconvenient by the majority of the local intelligentsia, we reflected especially in light of studies made by Said and Bourdieu, for example the relevance of this "imperialist attitude" articulated by this Lusitanian elite and the importance to Portugal of maintaining this hegemony in their (old) colony.